The Anatomical Society core anatomy syllabus for pharmacists: outcomes to create a foundation for practice. Issue 5 (8th February 2018) - Finn, Gabrielle M.; Hitch, Geeta; Apampa, Buge; Hennessy, Catherine M.; Smith, Claire F.; Stewart, Jane; Gard, Paul R
Abstract: The Anatomical Society has developed a series of learning outcomes that 'experts' within the field would recommend as core knowledge outputs for a Master's Degree Programme in Pharmacy (MPharm) within the UK. Using the Anatomical Society core gross anatomy syllabus for medical anatomy as a foundation, a modified Delphi technique was used to develop outcomes specific to pharmacy graduates. A Delphi panel consisting of medical practitioners, pharmacists and anatomists ( n  = 39) was created and involved 'experts' representing 20 UK Higher Education Institutions. The output from this study was 49 pharmacy‐specific learning outcomes that are applicable to all pharmacy programmes. The new MPharm anatomy syllabus offers a basic anatomical framework upon which pharmacy educators can build the necessary clinical practice and knowledge. These learning outcomes could be used to develop anatomy teaching within an integrated curriculum as per requirements of the General Pharmaceutical Council (GPhC).